2016
DOI: 10.21746/aps.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ethnomedicinal Plant Diversity of Una and Hamirpur District of Himachal Pradesh, India: An Ethno-ecological approach

Abstract: The present study was conducted to explore ethnobotanical diversity and importance of local plants harnessing for medicinal purposes by the local people of Una and Hamirpur district which lies at Shivalik hills or outer Himalayas in Himachal Pradesh, India. We recorded total 159 plant species of 138 genera belonging to 68 families which were used to cure more than 33 different types of ailments. Across family-wise distribution, most important useful plants were recorded from ten families: Asteraceae, Euphorbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…In general, there are many evidences given in the earlier literature as well as from scientific documents that combined form of a plant species can be a better and effective remedy for the treatment of ailments (Chand et al, 2016). In present study, Powder of dried aerial whole part of Aloe vera plant is mixed with equal amount of Phyllanthes emblica, Terminalia bellarica and Terminalia chebulla fruit powder and required amount of black salt to cure the constipation and stomach disorder.…”
Section: Preparation and Formulation For Medicinementioning
confidence: 91%
See 2 more Smart Citations
“…In general, there are many evidences given in the earlier literature as well as from scientific documents that combined form of a plant species can be a better and effective remedy for the treatment of ailments (Chand et al, 2016). In present study, Powder of dried aerial whole part of Aloe vera plant is mixed with equal amount of Phyllanthes emblica, Terminalia bellarica and Terminalia chebulla fruit powder and required amount of black salt to cure the constipation and stomach disorder.…”
Section: Preparation and Formulation For Medicinementioning
confidence: 91%
“…17 Page | 1900 -----------------------(iv) NC is = Total citations of ith species given by each informant, TI n = Total number of informants involved during the survey for all plant species.…”
Section: Factor Informant Consensusmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, diversifying the food chain to include these neglected species could be an effective tool to improve overall human nutrition and health . Bamboo is one such neglected plant, which has great potential to combat malnutrition and improve health due to its nutritious and health‐enhancing properties . Freshly harvested bamboo shoots are good source of water, proteins, fiber, vitamins, and amino acids .…”
Section: Introductionmentioning
confidence: 99%
“…Himachal Pradesh is blessed with rich plant diversity including medicinal and other useful plants (Sharma, 1976;Uniyal and Chauhan, 1982;Chauhan, 1999 andGulati et al, 2004). Previous ethnobotanical studies had revealed indigenous knowledge of medicinal species used by the people in different parts of the state (Singh, 1999;Thakur, 2001;Sood et al, 2001;Sharma et al, 2003;Samant et al, 2007;Kaur et al, 2011;Chand et al, 2016). However, a specific report on anti-diabetic medicinal plants from Una district has not figured in any earlier text.…”
Section: Introductionmentioning
confidence: 99%